Challenges and Opportunities of Trilateral Partnership to Promote Greater Local Ownership and Sustainability: the Experience of the USA, Brazil and Mozambique Food Security Project, 2011–2015 - Schmink, Marianne; Smart, Jenny; Sitoe, Isabel; Bowen, Walter; Silva, Henoque Ribeiro; Ecole, Carvalho Carlos; Haber, Lenita (2019)
Presented at “Knowledge for Sustainable Development: the Research-Policy Nexus” Global Sustainable Development Network Conference in Bonn, Germany, 23-25 October 2019.